Production of Miscanthus x giganteus for Biofuel - John Erickson; Curtis Rainbolt; Yoana Newman; Lynn Sollenberger; Zane Helsel (EDIS, 2012)
The bioenergy industry has primarily used Miscanthus for combustion in power plants. It has desirable properties of low water and ash contents following a dry-down period before harvest. Current research is focused on its potential as a biomass crop for direct combustion and for lignocellulosic conversion to ethanol and other biofuels. This revised 3-page fact sheet was written by John Erickson, Curtis Rainbolt, Yoana Newman, Lynn Sollenberger, and Zane Helsel, and published by the UF Department of Agronomy, September 2012.